Ionization of the hydrogen molecular ion H2+ by twisted light. (August 2015) - Peshkov, A A; Fritzsche, S; Surzhykov, A
Synopsis: The ionization of the hydrogen molecular ion H2 + by twisted Bessel light has been theoretically investigated. Special attention is paid to scenario where the twisted radiation interacts with a macroscopic target which consists of randomly distributed but aligned H2 + molecules. We demonstrate for this case that the angle-differential photoionization cross section is sensitive to the transverse momentum of the incident light and alignment angle of molecules.